Effects of biocholine powder supplementation in ewe lambs: Growth, rumen fermentation, antioxidant status, and metabolism - Leal K.W.* (2021)
© 2020 The AuthorsThe objective of this study was to evaluate the effects of biocholine powder (BP) added to the concentrate of ewe lambs on growth, rumen fermentation, antioxidant status, and metabolism. Forty-eight Lacaune lambs were divided 3 treatments: T0, T4, and T8, representing 0, 4, and 8 g of BP per animal/day added to the concentrate, respectively. The T4 and T8 lambs had greater average daily gain from d 0–75 (0.22, 0.25, and 0.26 kg/d for T0, T4 and T8, respectively). T4 and T8 lambs had higher methylene blue test results (indicating microbiological activity), and the higher effects were detected for T8 lambs. The BP in lamb's diet increased the ruminal concentration of propionate (T4 and T8). The T8 lambs had greater serum activity of superoxide dismutase and glutathione transferase, and lower reactive oxygen species levels. We conclude that BP is a biotechnological additive with high nutritional potential.